Training and Support for Parents of Children with Emotional and Behavioral Disorders - Lukowiak, Twila (Journal of the American Academy of Special Education Professionals, 2010)
Parents and guardians of children with the special education eligibility of emotional disturbance often have difficulties knowing how to appropriately and effectively handle their children’s disruptive behaviors at home. Even though their children may be making behavioral improvements in school, often times their behaviors are still very problematic at home. So why is it that children with emotional and behavioral disorders (EBD) may display more appropriate behaviors in the school setting than they do at home? One possible explanation is that the parents and guardians of these children do not have the same training and knowledge concerning effective behavioral strategies typically implemented in behavioral classrooms. This article explains the dire need for school districts to implement training sessions and support groups for parents and guardians of children with EBD. The article also details possible topics for training sessions and provides ideas concerning compensation for presenters.